DEVELOPMENT AND CHARACTERIZATION OF MEDICAL PHANTOMS FOR ULTRASOUND IMAGING BASED ON CUSTOMIZABLE AND MOULDABLE POLYVINYL ALCOHOL CRYOGEL-BASED MATERIALS AND 3-D PRINTING: APPLICATION TO HIGH-FREQUENCY CRANIAL ULTRASONOGRAPHY IN INFANTS - Elvira, Luis (2019)
This work presents an affordable and easily customizable methodology for phantom manufacturing, which can be used to mimic different anatomic organs and structures. This methodology is based on the use of polyvinyl alcohol-based cryogels as a physical substitute for biologic soft tissues and of 3-D printed polymers for hard tissues, moulding and supporting elements. Thin and durable soft-tissue mimicking layers and multilayer arrangements can be obtained using these materials. Special attention was paid to the acoustic properties (sound speed, attenuation coefficient and mechanical impedance) of the materials developed to simulate soft tissues. These properties were characterized as a function of the additives concentration (propylene-glycol and alumina particles). The polyvinyl alcohol formulation proposed in this work is stable over several freeze-thaw cycles, allowing the manufacturing of multilayer materials with controlled properties. The manufacturing methodology presented was applied to the development of a phantom for high-frequency cranial ultrasonography in infants. This phantom was able to reproduce the main characteristics of the ultrasound images obtained in neonates through the anterior fontanel, down to 8-mm depth. (C) 2019 World Federation for Ultrasound in Medicine & Biology. All rights reserved.